Stability analysis of paper machine headbox using a new PI(D) tuning technique - Saini, Parvesh; Kumar, Rajesh (International Journal of Engineering and Technology, 2018)
Paper, today, has made an important place in human’s life. Being an important commodity, paper has different qualities throughout the globe. As the technology is advancing, paper is being used for numerous applications and need of good quality paper is increasing daily. To have papers of desirable quality, paper machines with latest technology are developed. However, the quality of paper principally depends on the prime element of paper machine i.e. Headbox. Headbox is a highly non-linear Multi-input Multi-output (MIMO) component of paper machine and requires a precise control of its major parameters to get good quality papers which eventually responsible for sustained economy of pulp and paper industry. In past few decades, headbox has been a key element for research. Researchers have developed different control algorithms for headbox. This paper presents stability analysis of paper machine headbox using a new technique of Proportional – Integral – Derivative (PID) controller design namely Extended Forced Oscillation method (EFO). Also, the paper presents a comparative analysis of EFO method of PID tuning with the conventional Ziegler - Nichols(ZN) tuning technique based on transient characteristics and performance indices of headbox.